Flexible nuclear power and fluctuating renewables? — An analysis for decarbonized multi-vector energy systems - Leonard Göke; Alexander Wimmers; Christian von Hirschhausen (Energy Strategy Reviews, 2025)
Many governments consider new nuclear power plants to promote decarbonization. On the one hand, dispatchable nuclear plants can complement fluctuating generation from wind and PV. On the other hand, escalating construction costs and times raise economic concerns. This paper investigates the economic threshold at which nuclear plants are an efficient decarbonization option. Building on an extensive review of construction costs and times, we apply a detailed model of the European energy system to analyze the cost-efficient share of nuclear power in fully decarbonized energy systems in 2040. Our analysis finds that even if, reversing the historical trend, overnight construction costs of nuclear half to 4,000 US-$2018 per kW and construction times remain below ten years, the cost-efficient share of nuclear power in European electricity generation is only around 10%. Nuclear plants must operate inflexibly and at capacity factors close to 90% to recover their investment costs, implying that operational flexibility – even if technically possible – is not economically viable. As a result, grid infrastructure, flexible demand in multi-energy systems, and storage are more efficient options for integrating fluctuating wind and photovoltaic generation. The findings suggest that nuclear power should not be relied on for flexibility in future power systems.